2020
DOI: 10.30994/jqwh.v3i2.66
|View full text |Cite
|
Sign up to set email alerts
|

Pemenuhan Gizi dengan Kualitas Tidur pada Bayi Usia 6-9 Bulan di Puskesmas Bangsal Kabupaten Mojokerto

Abstract: Hasil penelitian menunjukkan bayi usia 6 bulan sudah mengalami gizi mencukupi kebutuhan gizi kurang sebanyak 18 bayi (46,2%) dan mengalami gangguan tidur sebanyak 15 bayi (38,5%). Untuk bayi yang memenuhi kebutuhan gizi lebih sebanyak 9 bayi (23,1%), semua bayi mengalami gangguan saat tidur. Kemudian bayi yang mendapat gizi cukup memenuhi kebutuhan sebanyak 12 bayi (30,8%), sehingga yang mendapat gangguan tidur sebanyak 11 bayi (28,2%). Hasil uji pearson chi squre dengan menggunakan SPSS didapatkan nilai P Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Based on research conducted by The NICHD Early Child Care Research in America shows for babies less than 6 months old who experience sleep problems as much as 53% while for babies aged 15 months as much as 44% (Susanti, I. Y.;Hety, 2020). Data in Indonesia is quite a lot of babies who experience sleep problems, which is around 44.2%.…”
Section: Univariate Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Based on research conducted by The NICHD Early Child Care Research in America shows for babies less than 6 months old who experience sleep problems as much as 53% while for babies aged 15 months as much as 44% (Susanti, I. Y.;Hety, 2020). Data in Indonesia is quite a lot of babies who experience sleep problems, which is around 44.2%.…”
Section: Univariate Analysismentioning
confidence: 99%
“…Data in Indonesia is quite a lot of babies who experience sleep problems, which is around 44.2%. More than 72% of parents do not consider sleep disorders in infants to be a problem (Susanti, I. Y.;Hety, 2020).…”
Section: Univariate Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that 30% of mothers reported the prevalence of sleep disorders in their infants. In Indonesia, around 44.2% of children experience sleep disturbances in the form of frequent nighttime awakenings (Susanti & Hety, 2020). Meanwhile, research according to (Sinaga & Laowo, 2020), on the effect of baby massage on the quality of sleep of infants aged 0 -6 months at BPM Pera, Medan Tutungan District.…”
Section: Introductionmentioning
confidence: 99%